Identification of Therapeutic Covariant MicroRNA Clusters in Hypoxia-Treated Cardiac Progenitor Cell Exosomes Using Systems Biology. Issue 2 (16th January 2015) - Gray, Warren D.; French, Kristin M.; Ghosh-Choudhary, Shohini; Maxwell, Joshua T.; Brown, Milton E.; Platt, Manu O.; Searles, Charles D.; Davis, Michael E.
<x xml:space="preserve">Abstract</x> Rationale: Myocardial infarction is a leading cause of death in developed nations, and there remains a need for cardiac therapeutic systems that mitigate tissue damage. Cardiac progenitor cells (CPCs) and other stem cell types are attractive candidates for treatment of myocardial infarction; however, the benefit of these cells may be as a result of paracrine effects. Objective: We tested the hypothesis that CPCs secrete proregenerative exosomes in response to hypoxic conditions. Methods and Results: The angiogenic and antifibrotic potential of secreted exosomes on cardiac endothelial cells and cardiac fibroblasts were assessed. We found that CPC exosomes secreted in response to hypoxia enhanced tube formation of endothelial cells and decreased profibrotic gene expression in TGF-β–stimulated fibroblasts, indicating that these exosomes possess therapeutic potential. Microarray analysis of exosomes secreted by hypoxic CPCs identified 11 miRNAs that were upregulated compared with exosomes secreted by CPCs grown under normoxic conditions. Principle component analysis was performed to identify miRNAs that were coregulated in response to distinct exosome-generating conditions. To investigate the cue–signal–response relationships of these miRNA clusters with a physiological outcome of tube formation or fibrotic gene expression, partial least squares regression analysis was applied. The importance of each up- or downregulated miRNA on physiological outcomes was determined. Finally, to validate the model, we delivered exosomes after ischemia–reperfusion injury. Exosomes from hypoxic CPCs improved cardiac function and reduced fibrosis. Conclusions: These data provide a foundation for subsequent research of the use of exosomal miRNA and systems biology as therapeutic strategies for the damaged heart.